Consumer attitude and purchase intention toward rooftop photovoltaic installation: The roles of personal trait, psychological benefit, and government incentives. Issue 1 (February 2020) - Sun, Pi-Chuan; Wang, Hsueh-Mei; Huang, Hsien-Long; Ho, Chien-Wei
Rooftop photovoltaic system is a cheap and abundant energy source that addresses the threat of global warming, and its future success relies on government incentives and marketing strategies designed to improve consumers' benefit perception. The present study aimed to examine the relationship among personal traits (including environmental concern, an ecological lifestyle, and consumer innovativeness), psychological benefits (including a warm glow and a "nature experience"), attitudes toward rooftop photovoltaic, government incentives, and intentions to install rooftop photovoltaic. Empirical data were collected from one nationwide company in Taiwan, and 300 valid questionnaires were collected. The collected data were analyzed using a structural equation model. The results show that an ecological lifestyle, consumer innovativeness, and warm glow affect rooftop photovoltaic installation intention through the attitude toward rooftop photovoltaic. Moreover, government incentives have the strongest influence on this intention. This study integrates personal traits, psychological benefits, attitudes toward rooftop photovoltaic, government incentives, and intentions to install rooftop photovoltaic in a model from the consumer perception theory perspective; it expands the theory regarding planned behavior in the solar photovoltaic research field. This research also provides suggestions for government policymakers and offers a strong theoretical and practical framework for photovoltaic industry marketers.